2018
DOI: 10.1038/s41391-018-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Decipher Test for predicting adverse pathology in candidates for prostate cancer active surveillance

Abstract: AbstactBackgroundMany men diagnosed with prostate cancer are active surveillance (AS) candidates. However, AS may be associated with increased risk of disease progression and metastasis due to delayed therapy. Genomic classifiers, e.g., Decipher, may allow better risk-stratify newly diagnosed prostate cancers for AS.MethodsDecipher was initially assessed in a prospective cohort of prostatectomies to explore the correlation with clinically meaningful biologic characteristics and then assessed in diagnostic biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 23 publications
1
50
1
1
Order By: Relevance
“…Retrospective case cohort studies have shown that these assays provide prognostic information independent of NCCN or CAPRA risk groups, which include likelihood of death with conservative management, likelihood of biochemical recurrence after radical prostatectomy or EBRT, likelihood of adverse pathologic features after radical prostatectomy, and likelihood of developing metastasis after operation or salvage EBRT. [131][132][133][134][135][136][137][138][139][140] A prospective, clinical utility study of 3,966 patients newly diagnosed with localized prostate cancer found that the rates of active surveillance increased with use of a tissue-based gene expression classifier. 141 Active surveillance rates were 46.2%, 75.9%, and 57.9% for those whose classifier results were above the specified threshold, below the threshold, and those who did not undergo genomic testing, respectively (P,.001).…”
Section: Tumor Multigene Molecular Testingmentioning
confidence: 99%
“…Retrospective case cohort studies have shown that these assays provide prognostic information independent of NCCN or CAPRA risk groups, which include likelihood of death with conservative management, likelihood of biochemical recurrence after radical prostatectomy or EBRT, likelihood of adverse pathologic features after radical prostatectomy, and likelihood of developing metastasis after operation or salvage EBRT. [131][132][133][134][135][136][137][138][139][140] A prospective, clinical utility study of 3,966 patients newly diagnosed with localized prostate cancer found that the rates of active surveillance increased with use of a tissue-based gene expression classifier. 141 Active surveillance rates were 46.2%, 75.9%, and 57.9% for those whose classifier results were above the specified threshold, below the threshold, and those who did not undergo genomic testing, respectively (P,.001).…”
Section: Tumor Multigene Molecular Testingmentioning
confidence: 99%
“…Over the last two decades, prostate cancer remains the most diagnosed neoplasm in American men, representing approximately 20% of all new diagnoses in 2019 [1]. Overtreatment of newlydiagnosed, indolent prostate cancers detected by rising levels of prostate-specific antigen (PSA) has been mitigated by increasingly widespread adoption of active surveillance, MRI-targeted biopsies, nomograms, and molecular tests for assessing the risk posed by unsampled higher grade disease [2][3][4][5]. While the absence of adverse pathological features, such as high Gleason score or seminal vesicle invasion, from biopsy is associated with improved outcomes following definitive therapy (surgery or radiation), sampling errors may lead to underestimation of the risk of biochemical recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective was to evaluate Decipher's prognostic ability to predict AP (defined as GG 3−5, pT3b or higher, or lymph node invasion (LNI) [14]) at RP within the NCCN F-IR group while accounting for clinical risk using the linear, extensively validated Cancer of the Prostate Risk Assessment (CAPRA [16]) score. In addition to this definition of AP, we also evaluated two alternatives: (1) GG 3−5 as an isolated endpoint, and (2) expanding the definition of adverse pathology to include extraprostatic extension (i.e., GG 3−5, ≥pT3a, or LNI (AP-II)).…”
Section: Discussionmentioning
confidence: 99%
“…Specimen collection and sample processing were conducted as described previously [13,14]. The prostate needle biopsy core with highest grade and percentage of core involved with tumor was sampled for the Decipher assay, a CAP/CLIA clinical-grade whole-transcriptome assay.…”
Section: Study Cohortmentioning
confidence: 99%